Colonialism, Land, Ethnicity, and Class: Namibia after the Second National Land Conference. Issue 1 (April 2019) - Melber, Henning
Since independence in March 1990, the unequal distribution and ownership of land as a leftover of colonial-era dispossession and appropriation has been a major issue of sociopolitical contestation in Namibia. This article summarises the structural colonial legacy and the efforts made towards land reform. Reference points are the country's first national land reform conference in 1991 and the second national land reform conference in October 2018. The analysis points to the contradictory factors at play, seeking to contextualise land reform in between the colonial legacy of racial discrepancies and ethnicity as well as class, as more contemporary influencing factors.